1989
DOI: 10.1002/ijc.2910440408
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and bladder cancer in males: Increased risk for inhalers and smokers of black tobacco

Abstract: Relationships between risk of bladder cancer and tobacco smoking were assessed from a hospital-based case-control study conducted in France from 1984 to 1987. Smoking history was analyzed for 954 male patients (477 cases and 477 controls). The odds ratio (OR) of bladder cancer was estimated at 3.95 for all smokers vs. non-smokers. The risk increased with duration of smoking and with average daily cigarette consumption, but there was a significant interaction between these 2 parameters, since the risk only incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
63
0
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 15 publications
6
63
0
3
Order By: Relevance
“…Both mainstream and sidestream tobacco smoke contain nanogram quantities of carcinogenic aromatic amines, such as ortho-toluidine, 2-naphthylamine, and 4-ABP, for example, mainstream smoke from a nonfiltered cigarette contains 160, 1.7, and 4.6 nanograms of the respective chemicals (10,11). The elevated risk of bladder cancer in smokers is ascribed to their exposure to aromatic amines, with smokers of black (air cured) tobacco being at higher risk than smokers of blond (flue cured) tobacco (12)(13)(14). The latter finding accords with the richer content of aromatic amines in black tobacco products than blond tobacco products (10).…”
Section: Introductionmentioning
confidence: 99%
“…Both mainstream and sidestream tobacco smoke contain nanogram quantities of carcinogenic aromatic amines, such as ortho-toluidine, 2-naphthylamine, and 4-ABP, for example, mainstream smoke from a nonfiltered cigarette contains 160, 1.7, and 4.6 nanograms of the respective chemicals (10,11). The elevated risk of bladder cancer in smokers is ascribed to their exposure to aromatic amines, with smokers of black (air cured) tobacco being at higher risk than smokers of blond (flue cured) tobacco (12)(13)(14). The latter finding accords with the richer content of aromatic amines in black tobacco products than blond tobacco products (10).…”
Section: Introductionmentioning
confidence: 99%
“…The numbers are generally small, and the confidence intervals of the odds ratios are large; nevertheless, the qualitative consistency of the findings is intriguing (see also reference 4 for a review In a molecular epidemiology investigation in which we were involved (6), we reported that the quantities of hemoglobin adducts with 3-aminobiphenyl (3-ABP) and 4-ABP were related to the quantity of cigarettes smoked and, in the case of 4-ABP, also to the kind of tobacco smoked (air or flue cured). Air-cured tobacco is known to contain larger amounts of arylamines than flue-cured product and has also been found to be associated with higher risks of bladder cancer in three epidemiological investigations (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmaya göre erkeklerde en sık görülen üçüncü kanser türü olup , tüm kanserler içindeki payı %8.5' tir. Kadınlarda ise 13. sı-radadır [3,4]. Mesane kanserinin %75-85' inde hastalık, mukoza (evre Ta-CIS) veya submukozaya (evre T1) sınırlıdır.…”
Section: Introductionunclassified